Transformation of Offline to Online Learning through the Development of Econometric Teaching Materials and Their Impact on Student Learning Outcomes - Putri Sari MJ Silaban; Joko Suharianto; Aurora Elise Putriku; Sabda DN Siahaan; Jessica Putri Br. Sembiring (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
One form of transformation of offline to online learning is the change of printed learning materials to non-printed teaching materials. The hope is that it can facilitate and support the management of online learning. In general, this study aims to determine the level of feasibility and effectiveness teaching materials in econometrics courses can improve student learning outcomes.   This study uses research and development (R&D) methods using the ADDIE model. This research was conducted on fifth-semester students of class A who took econometrics courses in the economic education study program in the 2021/2022 academic year. For a small trial sample, 30 students were taken. The results of the effectiveness test concluded that student learning outcomes after using econometrics teaching materials were higher than the results of student pretests. This shows that the non-printed Econometrics teaching materials produced are proven to be effective in improving student learning outcomes.